Health Status of Bachelor of Physical Education Degree Students Amidst the COVID-19 Pandemic - Carlo Manosa; Christian Kyle Pineda; Jeremy Jed Namora; Cheryl Daga-as (Indonesian Journal of Multidiciplinary Research, 2022)
This study was conducted to know the health status of bachelor of physical education degree (BPED) students in the midst of the COVID-19 pandemic in terms of their physical, mental, and social well-being. This study has thirty (30) respondents who were BPED Students of Sultan Kudarat State University, ACCESS Campus and were selected randomly. The instrument used to gather the data and information was a survey questionnaire regarding physical, mental, and social well-being. The data gathered from the study were treated using frequency distribution and weighted mean, tabulated, analyzed, and interpreted. Then the results of the study were tabulated, analyzed, and interpreted. The results of the study proved that knowing the level of Health Status of BPED Students in the midst of the COVID-19 Pandemic is generally positive and good. Furthermore, the level of the health status of students in terms of physical well-being was affected by the pandemic. In addition, the feeling to take suicide was never observed by the students which means that students still manage their mental well-being in the midst COVID-19 pandemic. Lastly in social well-being, following the safety protocols was always observed by the students and their families. The teachers and school administrators should learn further the different strategies to impart help to students to maintain their level of health status in the midst of a pandemic. Researchers must improve and prove that these factors have a big and great impact on the students and may help them to improve their performance in the future.